ANALISIS KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Nadysha Imani Hartanto (2022)
The purpose of this study was to determine the effect of investment decisions which were analysed using three financial ratios Price to Earning Ratio (PER), Debt to Equity Ratio (DER), and Return on Equity (ROE) on company value as measured by Price to Book Value (PBV) for the period 2017 to 2021. This research is a quantitative study and the population used is energy sector companies listed on the IDX. The sampling technique used the purposive sampling method so that 42 companies were obtained as samples. Data analysis used the E- Views 12 application with a significance level of 5%. The research results obtained are investment decisions (PER) have no effect on firm value, funding decisions (DER) and profitability (ROE) have an effect on firm value.